Reactivity of imidazolidin-4-one derivatives of primaquine - Chambel, Paula (2015)
In contrast to peptide-based imidazolidin-4-ones, those synthesized from N-(alpha-aminoacyl) derivatives of the antimalarial drug, primaquine and ketones are unexpectedly stable in pH 7.4 at 37 degrees C. The kinetics of hydrolysis of primaquine-based imidazolidin-4-ones were investigated in the pH range 0.3-13.5 at 60 degrees C. The hydrolysis to the parent alpha-aminoacylprimaquine is characterized by sigmoidal-shaped pH-rate profiles, reflecting the spontaneous decomposition of both unionized and protonated (at N-1) forms of the imidazolidin-4-one. The kinetically determined pK(a) values are ca. 3.6-4.0, i.e., 4 pKa units lower than those of amino acid amides, thus implying that hydrolysis of imidazolidin-4-ones at pH 7.4 involves the unionized form. Reactivity of this form decreases with the steric crowding of the amino acid alpha-substituent. In contrast, the rate constant for the spontaneous decomposition of the unionized form increases sharply for imidazolidin-4-ones derived from cyclic ketones, an observation that can be explained by the I-strain (internal strain) effect. These results are consistent with a mechanism of hydrolysis involving an S(N)1-type unimolecular cleavage of the imidazolidin-4-one C2-N3 bond with departure of an amide-leaving group. The mechanism for the decomposition of the protonated imidazolidin-4-one is likely to involve an amide-carbonyl oxygen protonated species, followed by the C2-N3 bond scission, as supported by computational studies. The results herein presented suggest that imidazolidin-4-ones derived from simple N-alkyl alpha-aminoamides are too stable and therefore, may be useful as slow drug release prodrugs. (c) 2006 Elsevier Ltd. All rights reserved.